Physiological Stress Mediates the Honesty of Social Signals - Bortolotti, Gary R. (Public Library of Science, 2009)
BACKGROUND: Extravagant ornaments used as social signals evolved to advertise their bearers' quality. The Immunocompetence Handicap Hypothesis proposes that testosterone-dependent ornaments reliably signal health and parasite resistance; however, empirical studies have shown mixed support. Alternatively, immune function and parasite resistance may be indirectly or directly related to glucocorticoid stress hormones. We propose that an understanding of the interplay between the individual and its environment, particularly how they cope with stressors, is crucial for understanding the honesty of social signals. METHODOLOGY/PRINCIPAL FINDINGS: We analyzed corticosterone deposited in growing feathers as an integrated measure of hypothalamic-pituitary-adrenal activity in a wild territorial bird, the red grouse Lagopus lagopus scoticus. We manipulated two key, interrelated components, parasites and testosterone, which influence both ornamentation and fitness. Birds were initially purged of parasites, and later challenged with parasites or not, while at the same time being given testosterone or control implants, using a factorial experimental design. At the treatment level, testosterone enhanced ornamentation, while parasites reduced it, but only in males not implanted with testosterone. Among individuals, the degree to which both parasites and testosterone had an effect was strongly dependent on the amount of corticosterone in the feather grown during the experiment. The more stressors birds had experienced (i.e., higher corticosterone), the more parasites developed, and the less testosterone enhanced ornamentation. CONCLUSIONS/SIGNIFICANCE: With this unique focus on the individual, and a novel, integrative, measure of response to stressors, we show that ornamentation is ultimately a product of the cumulative physiological response to environmental challenges. These findings lead toward a more realistic concept of honesty in signaling as well as a broader discussion of the concept of stress.